Recurrent p16-Positive Human Papillomavirus (HPV) Associated Oral Lesions Treated with a Diode Laser: A Case Report - Pezzi, Margherita Eleonora; Passerini, Pietro; Frontera, Marco; Vescovi, Paolo; Meleti, Marco (Journal of Dentistry Indonesia, 2019)
Human papilloma virus (HPV) family include approximately 150 known subtypes of viruses that can infect humans and other animals. Among these, HPV-16 is known for its association with oral squamous cell carcinoma (OSCC), particularly within the oropharynx. HPV 16 genotype can be found in a variety of oral lesions, its presence being frequently observed in papillomas. Treatment of oral papillomas can sometimes be challenging as HPVs tend to shed to different oral sites, causing multifocal lesions. Moreover, HPV-related lesions tend to recur if incompletely removed. Several light-amplification by stimulated emission of radiation (laser) wavelenghts are currently used in dentistry as surgical tools both on soft and hard tissues. Among these diode laser is one of the most used. Advantages of laser surgery include, among others, good precision, optimal hemostasis, possible biostimulative and antibacterial effects and a reduced post-operative discomfort. Here we report the case of a 26-year old man with multiple, recurrent p-16 positive papillomatous lesions, which was successfully treated through diode laser (445 nm) surgery.